Estimation of dose and elapsed time after unrecognized high-dose radiation exposure using the continuous-wave optically stimulated luminescence from Mg2SiO4:Tb. (December 2020) - Yasuda, Hiroshi; Discher, Michael
Abstract: For precisely estimating dose and elapsed time after an unrecognized high-dose radiation exposure in radiological emergency, applicability of the continuous-wave optically stimulated luminescence (CW-OSL) signals from Mg2 SiO4 :Tb (MSO) was investigated. Small disks of MSO were irradiated with β-rays from a Sr-90 source and their CW-OSL signals were analysed. The CW-OSL curves obtained by stimulation with a blue light (λ = 458 nm) at 5, 10, 20, 50 and 1119 h after irradiation indicated that they have short- and long-life components; each component was empirically deconvoluted to the sum of two exponential functions. Through repetitive regression analyses on those curves, a practical method for estimating the dose and elapsed time after an unrecognized radiation exposure was proposed. Results of blind tests indicated that the accuracy of absorbed dose estimation using this method was satisfactory while the estimated elapsed times were accompanied with considerable uncertainties. Highlights: Radiation induced CW-OSL curves from Mg2 SiO4 :Tb were deconvoluted to two components. A method using CW-OSL for estimating dose and elapsed time of accidental exposure was proposed. Practicality and accuracy of the proposed method were partially confirmed through blind tests.